Accuracy of UTE‐MRI‐based patient setup for brain cancer radiation therapy. Issue 1 (24th December 2015) - Yang, Yingli; Cao, Minsong; Kaprealian, Tania; Sheng, Ke; Gao, Yu; Han, Fei; Gomez, Caitlin; Santhanam, Anand; Tenn, Stephen; Agazaryan, Nzhde; Low, Daniel A.; Hu, Peng
Abstract : Purpose: Radiation therapy simulations solely based on MRI have advantages compared to CT‐based approaches. One feature readily available from computed tomography (CT) that would need to be reproduced with MR is the ability to compute digitally reconstructed radiographs (DRRs) for comparison against on‐board radiographs commonly used for patient positioning. In this study, the authors generate MR‐based bone images using a single ultrashort echo time (UTE) pulse sequence and quantify their 3D and 2D image registration accuracy to CT and radiographic images for treatments in the cranium. Methods: Seven brain cancer patients were scanned at 1.5 T using a radial UTE sequence. The sequence acquired two images at two different echo times. The two images were processed using an in‐house software to generate the UTE bone images. The resultant bone images were rigidly registered to simulation CT data and the registration error was determined using manually annotated landmarks as references. DRRs were created based on UTE‐MRI and registered to simulated on‐board images (OBIs) and actual clinical 2D oblique images from ExacTrac™. Results: UTE‐MRI resulted in well visualized cranial, facial, and vertebral bones that quantitatively matched the bones in the CT images with geometric measurement errors of less than 1 mm. The registration error between DRRs generated from 3D UTE‐MRI and the simulated 2D OBIs or the clinical oblique x‐ray images was also less than 1 mm for all patients. Conclusions: UTE‐MRI‐based DRRs appear to be promising for daily patient setup of brain cancer radiotherapy with kV on‐board imaging.